KAJIAN KERANGKA KERJA PEMERINGKATAN E-GOVERNMENT DI TINGKAT KABUPATEN/KOTAMADYA - Pipin Farida Ariyani (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2013)
Presidential Instruction No.3, 200 on Policy and Strategy of National Development, start to trigger the local government to immediately applying e-government in their area in order to utilize executing good governance and to improve the effective and efficient public service. Depkominfo(Minister of Communication and Information) provides a reference for developing and exploiting ICT in governance environment to measure the readiness of local government in developing the e-government. Reference made in the form of Indonesia e-government ranking (Pemeringkatan E-government Indonesia-PeGI). Since 2007, PeGI has been applied in provincial level. This research aim to see how they applied in regency/community level. The Research conducted is based on literature study and interview by using qualitative methodologies. The analysis conducted by assessing 5 dimension of PeGI’s. The Analysis look at the impact of conformity assessment inficator of PeGI, because there is an absence of impact assessment of 5 dimensions indicators of PeGI, which is still appropriate to be applied in regency/municipality level. In this research, it is recommended the regency/municipality level do the assessment of e-goverment in their regency/municipality by using indicator that stil fit. Keywords: PeGI, regency/municipality, indicator